DURABILITY OF ASPHALT CONCRETE MIXTURES USING DOLOMITE AGGREGATES - Al-Shalout, Imad; Аль-Шалоут, Імад; Аль-Шалоут, Имад (Харьковский национальный автомобильно-дорожный университет, 2015)
This study deals with the durability of asphalt concrete, including the effects of different gradations, compaction temperatures and immersion time on the durability potential of mixtures. The specific objectives of this study are: to investigate the effect of compaction temperature on the mechanical properties of asphalt concrete mixtures; investigate the effect of bitumen content and different aggregate gradations on the durability potential of bituminous mixtures.
ДОВГОВІЧНІСТЬ АСФАЛЬТОБЕТОННИХ СУМІШЕЙ З ВИКОРИСТАННЯМ ДОЛОМІТОВОГО ЩЕБЕНЮ
ДОЛГОВЕЧНОСТЬ АСФАЛЬТОБЕТОННЫХ СМЕСЕЙ С ИСПОЛЬЗОВАНИЕМ ДОЛОМИТОВОГО ЩЕБНЯ
Keywords: durability; asphalt concrete; dolomite; Marshall’s stability; aggregate gradation; compaction temperature; довговічність; асфальтобетонна суміш; доломіт; гранулометричний склад; температура ущільнення; долговечность; асфальтобетон; доломит; гранулометрический состав; температура уплотнения; 625.8